Indonesian Intra-Industrial Trade in ASEAN Region Countries - Deassy Apriani; Muhammad Teguh; Feny Marissa; Imelda Imelda (Department of Development Economics, Universitas Sriwijaya, 2022)
Through international trade, a country with other countries can interact and cooperate in the export and import of goods and services. Indonesia's export-import trade transactions with trading partner countries have undergone structural changes. This change was caused by the start of the industrialization process in the early 1990s. This study was conducted to find out how Indonesia's trade with its trading partners in ASEAN countries (Singapore, Malaysia, Thailand, Vietnam, and the Philippines). The data sources used in this study are United Nation Commodity Trade, World Bank, Statistics Indonesia from 2000 to 2018. Measuring the Grubel and Lloyd Index and using panel data regression. The findings indicate that the average GDP, real GDP per capita, and the exchange rate are positively related and have a significant effect on intra-industry trade. Meanwhile, the distance is not significant to intra industry trade.